The Effect of Competence and Workload on Motivation and Its Impact on the Performance of Civil Servants at the Regional Secretariat of the Regency of Dharmasraya - Irvan, Rita Maijuita; Heryanto, Heryanto (Archives of Business Research, 2019)
This study attempts to examine the effect of Competence and workload on work motivation and its impact on the performance of the Regional Secretariat staff in the Dharmasraya Regency.This study uses descriptive quantitative methods. The study population consisted of 60 employees at the Dharmasraya Regency Regional Secretariat. The data analysis technique is used path analysis. The results showed that the Competence and Workload had a positive and significant effect on Motivation and performance, as well as Motivation as an intervening variable capable of providing increased influence between Competence on Performance.The empirical findings indicate that for the performance of the Regional Secretariat staff in the Dharmasraya Regency, the Regional Secretariat of the Dharmasraya Regency needs to pay attention and focus more on improving the Competency and Workload factors.